PENGARUH ETIKA KERJA, PENGALAMAN KERJA DAN BUDAYA KERJA TERHADAP PRESTASI KERJA KARYAWAN PT. BERAU AGROTECH CIHAUR - Endah Prihartini; Dadang Sudirno (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
This research was conducted at PT. Berau Agrotech Cihaur which aims to determine the effect of work ethics, work experience and work culture on work performance of employees of PT. Berau Agrotech Cihaur. The problem that the author raises is whether work ethics, work experience and work culture have a significant partial and simultaneous effect on employee performance.. The method used in this study is a survey method with a descriptive analysis approach and verification. Collecting data by distributing questionnaires to respondents. The population in this study are employees of PT. Berau Agrotech Cihaur, with a total sample of 45 people. The sampling technique used is the non-probability sampling method. Analysis with a classical assumption test, multiple linear regression analysis, coefficient of determination and hypothesis testing ( a partial test and a simultaneous test) using SPSS 24 software for windows. The results of the research that has been carried out show that works ethics, work experience and work culture are in the good category and work performance is in the high category. Partially, it gives the results that work ethic has a positive and significant effect on work performance, work experience has a positive and significant effect on work performance, and work culture has a positive and significant effect on work performance. While simultaneously giving the result that works ethic, work experience and work culture has a positive and significant effect on work performance.